The Influence of Rewards, Punishments and Leadership Styles on Employee Performance at Plaza Auto Prima, West Jakarta - Saputra, Denny; Nurlinda, RA (Journal of Current Research In Multidisciplinary, 2025)
This study aims to examine the influence of reward, punishment, and leadership style on employee performance at PT Plaza Auto Prima in the West Jakarta area. Based on the hypothesis testing results, it was found that, simultaneously, these three variables have a significant impact on employee performance, with a significance value of 0.000, which is smaller than 0.05. Although punishment did not have a significant individual effect, the combination of reward, punishment, and leadership style collectively contributed positively to employee performance. The coefficient of determination (R²) of 58.8% indicates that other factors, such as job satisfaction and company culture, may also influence employee performance. Reward was found to have a significant positive effect, while punishment did not directly affect performance. Leadership style, particularly supportive and participative leadership, played a crucial role in enhancing employee performance. Based on these findings, it is recommended that the company focus more on well-targeted reward policies and the development of supportive leadership styles, while ensuring that punishment is applied proportionally and fairly. This study provides insights for PT Plaza Auto Prima in designing more effective policies to improve employee performance and create a more productive and innovative work environment.